Ignition of Fuel Slurries Based on Waste Products of Coal Processing and Oil Refining; Combustion, Explosion, and Shock Waves; Vol. 54, iss. 3 - Vershinina K. Yu. Kseniya Yurievna (2018, 2018)
Title screen